Euro Area Policies : Staff Report for the 2015 Article IV Consultations with Member Countries. (IMF Staff Country Reports; Country Report, 2015)
Context. The recovery is strengthening, underpinned by lower oil prices and the ECB's expanded asset purchase program. But the medium-term outlook remains weak, weighed down by the legacies of insufficient demand, lagging productivity, and weak bank and corporate balance sheets.